Formation of Students’ Ethics: Insights from Tadkirat al-Sami’ wa al-Mutakallim and Its Relevance to Contemporary Educational Theories - Harshad K, Muhammed; PK, Nabeela; Zahra B, Fathimath; Azeez P, Ajwa (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2025)
Contemporary education systems frequently face difficulties in nurturing students’ moral and ethical attitudes to support their overall development. One way to address this issue is by revisiting classical educational theories. This study explores how classical Islamic educational perspectives, particularly, Badr al-Din Ibn Jama’ah’s Tadkirat al-Sami’wa al-Mutakallim can be combined into current teaching practices to strengthen student ethics. Using qualitative content analysis, this research observes the core educational ideologies in this classical text to connect traditional insights with present-day educational needs. The study focuses on three main areas: Learning Excellence: Principles and Practices, Ethical framework of Student Conduct towards teachers; and Behavioral Approach of students in the classroom. The findings highlight the traits of successful learners, the importance of moral and ethical conduct, and the significance of spiritual refinement in education. According to the analysis, effective learning requires adapting instruction to students’ intellectual levels, preserving their dignity, and establishing a healthy and supportive classroom environment. Incorporating these classical principles can enrich modern education by promoting academic excellence and strong moral character.